In Time of Crisis, Britons and Germans Would Count on U.S. Most. - United States Information Agency. Office of Research and Media Reaction.; Fleury, Christopher J. (Tufts University. Tisch Library., 2019)
Recent USIA surveys in Britain, France, and Germany show that publics in these countries continue to appreciate the European alliance with the U.S. in the face of new security challenges. But many west Europeans remain uneasy with the extent of American influence over their countries.; Opinion Analysis M-74-98